Intercalated phases of transition metal dichalcogenides. (14th December 2020) - Wang, Ziying; Li, Runlai; Su, Chenliang; Loh, Kian Ping
Abstract: Two‐dimensional transition metal dichalcogenides (TMDs) play host to a wide range of novel topological states, such as quantum spin Hall insulators, superconductors, and Weyl semimetals. The rich polymorphism in TMDs suggests that phase engineering can be used to switch between different charge order states. Intercalation of atoms or molecules into the van der Waals gap of TMDs has emerged as a powerful approach to modify the properties of the material, leading to phase transition or the formation of substoichiometric phases via compositional tuning, thus broadening the electronic and optical landscape of these materials for a wide range of applications. Here, we review the current efforts in the preparation of intercalated TMD. The challenges and opportunities for intercalated TMDs to create a new device paradigm for material science are discussed.